Hybrid Networking in Microsoft Azure: A Comparative Analysis of Site-to-Site VPN and ExpressRoute - Shweta Kushwaha , Gaurav Tyagi , Gur Sharan Kant (Journal of Computational Analysis and Applications (JoCAAA), 2024)
Hybrid networking has become a crucial strategy for enterprises integrating on-premises infrastructurewith cloud environments. Microsoft Azure offers two primary hybrid connectivity solutions: Site-to-Site (S2S) VPNand ExpressRoute. S2S VPN leverages the public internet to establish